1967
DOI: 10.1017/s0021859600017792
|View full text |Cite
|
Sign up to set email alerts
|

Finishing steers on high-grain rations. Effects of type of silage, level of urea, vitamin A and cobalt supplementation on body-weight gain, feed efficiency and carcass composition

Abstract: Simple rations of sorghum grain and sorghum silage have been shown by Morris & O'Bryan (1965) and Morris (1966) to be suitable for the intensive finishing of steers in yards. With these rations, efficiency of feed conversion increased as the percentage grain in the final ration increased, attaining a maximum at 90 and 100 % grain. At all levels of grain feeding, groups of steers fed 60 g. urea per head daily had rates of gain and efficiencies of feed conversion superior to those not receiving urea. In the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1969
1969
2000
2000

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The hepatic concentration of vitamin A in the cows was measured on biopsy samples taken and analysed by the method described by Morris & Gartner (1967). Biopsy samples were taken at the commencement of all-grain feeding, at parturition and 70 days after parturition.…”
Section: Methodsmentioning
confidence: 99%
“…The hepatic concentration of vitamin A in the cows was measured on biopsy samples taken and analysed by the method described by Morris & Gartner (1967). Biopsy samples were taken at the commencement of all-grain feeding, at parturition and 70 days after parturition.…”
Section: Methodsmentioning
confidence: 99%
“…Burroughs et al (1963) reported The intensive production of beef from simple that the addition of vitamins E and K to no-hay rations of sorghum grain and sorghum silage was rations fed to cattle increased their rate of body reported by Morris & O'Bryan (1965), Morris (1966) weight gain. These workers also reported that and Morris & Gartner (1967). In these experiments selenium added at either 0-05 or 0-10 ppm to the grain was fed in a coarsely rolled condition and ration gave a similar growth response, and insilage in a chopped form.…”
Section: Introductionmentioning
confidence: 58%
“…A.C. (1960) with the modi-Beef production from sorghum grain and stubble fications described by Morris & Gartner (1967). Tocopherols and beta carotene were estimated by the methods of Nobile (1963) and Hausheer et al (1964) respectively.…”
Section: Analytical Methods and Body Weight Measurementmentioning
confidence: 99%